Genetically Modeled Mice with Mutations in Mitochondrial Metabolic Enzymes for the Study of Cancer - Piruat, José I.; Millán-Uclés, África (Frontiers in Oncology, 2014)
Mitochondrial dysfunction has long been implicated in progression of cancer. As a paradigm, the “Warburg effect,” which by means of a switch toward anaerobic metabolism enables cancer cells to proliferate in oxygen limiting conditions, is well established. Besides this metabolic transformation of tumors, it has been discovered that mutations in genes encoding mitochondrial proteins are the etiological factors in different types of cancer. This confers to mitochondrial dysfunction a causative role, rather than resultant, in tumor genesis beyond its role in tumor progression and development. Mitochondrial proteins encoded by tumor-suppressor genes are part of the succinate-dehydrogenase, the fumarate-hydratase, and the mitochondrial isocitrate-dehydrogenase enzymes, all of them participating in the Krebs cycle. The spectrum of tumors associated with mutations in these genes is becoming larger and varies between each enzyme. Several mechanisms of tumorigenesis have been proposed for the different enzymatic defects, most of them based on studies using cellular and animal models. Regarding the molecular pathways implicated in the oncogenic transformation, one of the first accepted theories was based on the constitutive expression of the hypoxia-inducible factor 1α (Hif1α) at normal oxygen tension, a theory referred to as “pseudo-hypoxic drive.” This mechanism has been linked to the three types of mutations, thus suggesting a central role in cancer. However, other alternative molecular processes, such as oxidative stress or altered chromatin remodeling, have been also proposed to play an onco-pathogenic role. In the recent years, the role of oncometabolites, a new concept emerged from biochemical studies upon these tumors, has acquired relevance as responsible for tumor formation. Nevertheless, the actual contribution of each of these mechanisms has not been definitively established. In this review, we summarize the results obtained from mouse strains genetically modified in the three different enzymes.